Fiscal Policy Effectiveness in a Small Open Economy : Estimates of Tax and Spending Multipliers in Paraguay - David, Antonio (Washington, D.C. : International Monetary Fund, 2017)
This paper presents estimates of fiscal multipliers in Paraguay following different econometric techniques and identification approaches. The results point to multipliers for capital expenditure that are substantially higher than multipliers for current expenditure. In addition, the evidence suggests that tax multipliers are close to zero when using conventional identification approaches, but estimates can be much larger when considering the 'narrative' approach. One implication of the results is that the balanced budget multiplier for Paraguay id est the effect of on output of an increase in expenditures (in particular capital expenditure) financed by taxes is likely to be positive.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet